Monetary and fiscal policy shocks on the stock market performance in the United States: evidence from the SVAR framework - Emamian, Aref; Mazlan, Nur Syazwani (TuEngr Group, 2021)
Evidence from studies of monetary and fiscal policy shocks on the stock market is still arguable not only for researchers but also for central banks and governments. In addition, the interaction between the two policies is very crucial; however, very few studies are available on this topic. In this regard, we examined the impact of monetary and fiscal policies shock on the stock market in the United States by utilising the annual data of the U.S. economy from the Federal Reserve, World Bank, and International Monetary Fund from 1980 until 2018. More specifically, we used the Structural Vector Autoregression (SVAR) framework to examine the dynamic relationship between fiscal and monetary policies and the stock market performance. Our results confirm that the interaction between both policies is crucial in understanding the stock market movements and both policies have a direct impact on the U.S. stock market. In the interpretation of stock market performance, the incorporation of the fiscal policy parameter does not add any significant values, suggesting that there is no significant difference when fiscal policy is removed from the model.